The association between diet quality index-international and inflammatory markers in Iranian overweight and obese women - Shiraseb, Farideh; Ebrahimi, Sara; Noori, Sahar; Bagheri, Reza; Alvarez-Alvarado, Stacey; Wong, Alexei; Mirzaei, Khadijeh (Frontiers in Nutrition, 2023)
Objectives: The present study was conducted to evaluate whether there is a link between diet quality index (DQI) and markers of systemic inflammation in Iranian overweight and obese women. Methods: This cross-sectional study included 200 Iranian overweight and obese women aged 18-48 years old. The DQI-international (DQI-I) comprises four main components: variety, adequacy, moderation, and overall balance. Blood samples were collected in a fasted state to measure inflammatory markers. Results: After adjusting for age, body mass index (BMI), physical activity, total energy intake, economic status, education, supplement intake, age of starting obesity, and history of body mass loss, a marginally significant negative association was observed between the homeostasis model assessment of insulin resistance (HOMA-IR) and the DQI-I (β: -0.015, 95% CI: -0.03, 0.000; p = 0.061). The results after adjustment showed that DQI-I has a negative association with high‐sensitivity C‐reactive protein (hs-CRP) concentrations (β: -0.031, 95% CI: -0.104, -0.031; p = 0.023).Furthermore, negative associations were observed between the adequacy component and levels of HOMA-IR (β: -0.025, 95% CI: -0.100, 0.047, p = 0.050) and hs-CRP (β: -0.615, 95% CI: -1.191, -0.020; p = 0.045).Also, negative associations were found between transforming growth factor-β (TGF-β) and balance score (β: -6.270, 95% CI: -39.211, -3.661, p = 0.020), as well as HOMA-¬¬IR (β: -0.080, 95% CI: -0.202, -0.000, p = 0.041) and chemoattractant protein-1 (MCP-1) (β: -0.562, 95% CI: -11.414, -0.282, p = 0.021) with the various component. Amarginally significant negative association between Galectin 3 (Gal-3) and moderation score (β: -0.451, 95% CI: -1.171, 0.060, p = 0.060) was found. In addition, a marginally significant inverse association was also established between hs-CRP and variety score (β: -0.311, 95% CI: -0.970, 0.001, p = 0.052). ROC CURVE analysis demonstrated that DQI-I might better predict HOMA-IR with a cut point of 3.13 (AUC = 0.698, 0.511-0.699, p = 0.050). Conclusions: These findings showed that higher adherence to diet quality and its components could probably be related to lowering the inflammatory markers considerably in overweight and obese women.